New Ways in Teaching Reading - Richard, R.Day (Virginia Teachers of English to Speakers of Other Languages)
This book is a collection of classroom activities, exercises, and suggestions for reading instruction, contributed by teachers who have used them in English-as-a-Second-Language (ESL) classes. It is organized in three major sections: extensive reading (reading a great deal of comprehensible material); intensive reading (focusing on specific skills and situations: pre-reading; prediction; comprehension; main ideas; organization and structure; scanning; skimming; academic reading; reading rate; literature; assessment/evaluation; vocabulary; dictionaries; cohesion; games and miscellaneous activities); and oral reading. The section on intensive reading is the most extensive, consisting of 2 to 20 activities for each skill or situation. Each idea is described briefly, with information given about appropriate proficiency level(s), specific aims, class time requirements, preparation time, needed resources, procedures, and caveats and options. Some entries also contain references for further reading. (MSE)
Keywords: classroom activities; Classroom Techniques; Educational Strategies; Offer hints,clues,recipes for success, words to the wise; Great activities for teaching extensive,intensive,and oral reading